Achievements of The Pre-Marital Screening Program at The Denpasar Barat I Public Health Center - Putu, Yuliantari; Made, Nyandra; Nyoman, Suarjana (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
The prospective bride and groom are strategic targets for health improvement during the preconception period. Public awareness of preconception health is still low. Counseling, information, and education are highly needed by prospective brides and grooms, especially as they prepare for a healthy pregnancy. The research method was conducted using a descriptive qualitative approach. Data was collected through interviews using a structured interview guide. The data was validated using data triangulation. Based on input indicators, the administrative staff needed includes midwives, doctors, laboratory analysts, health promotion personnel, and village heads/village staff. HRM competencies include knowledge, the premarital screening process, SOPs, and screening fees. The performance of program implementers is evaluated by the reproductive health program holders, cluster 2 managers, coordinating midwives, and health center heads. The source of funds comes from the State Budget and Regional Budgets, including the implementation of the premarital screening program. The target group is very supportive of the screening program. Based on process indicators, there are no supervision procedures yet. The planning SOP is approved by the head of the health center. The organization follows the SOP, which aligns with the work program in Cluster 2. The coverage of the premarital screening program is measured through reporting from the Kescatin application. Based on output indicators, whether the premarital screening program requirements have been met or not is only assessed based on the health certificates issued by the Puskesmas for the prospective bride and groom. It is hoped that the Puskesmas (Community Health Centers) will need to improve the quality of the premarital screening program by arranging a strategic plan to enhance the performance of program implementers and facilities and by collaborating with various sectors to achieve the set targets and goals.